A comparison of the clinical effectiveness and cost of specialised individually-delivered parent training for preschool attention-deficit/hyperactivity disorder and a generic, group-based programme: a multi-centre, randomised controlled trial of the New Forest Parenting Programme versus Incredible Years - Sonuga-Barke, Edmund J.S.; Barton, Joanne; Daley, David; Hutchings, Judy; Maishman, Tom; Raftery, James; Stanton, Louise; Bradbury, Cathy Laver; Chorozoglou, Maria; Coghill, David; Little, Louise; Ruddock, Martin; et al. (Springer, 2017)
Objective: To compare the efficacy and cost of specialised individually-delivered parent training (PT) for preschool children with attention-deficit/ hyperactivity disorder (ADHD) against generic group-based PT and treatment as usual (TAU). Design: Multi-centre, three-arm parallel group randomised controlled trial. Research Setting: National Health Service Trusts. Participants: Preschool children (33-54 months) fulfilling ADHD research diagnostic criteria. Interventions: New Forest Parenting Programme (NFPP) – 12 week individual, home-delivered ADHD PT programme; Incredible Years (IY) – 12 week group-based, PT programme initially designed for children with behaviour problems. Main outcome measures: Primary outcome - Parent ratings of child’s ADHD symptoms (Swanson, Nolan & Pelham Questionnaire - SNAP-IV). Secondary outcomes - teacher ratings (SNAP-IV) and direct observations of ADHD symptoms and parent/teacher ratings of conduct problems. NFPP, IY and TAU outcomes were measured at baseline (T1) and post-treatment (T2). NFPP and IY outcomes only were measured 6 months post treatment (T3). Researchers, but not therapists or parents, were blind to treatment allocation. Analysis employed mixed effect regression models (multiple imputation). Intervention and other costs were estimated using standardized approaches. Results: NFPP and IY did not differ on parent-rated SNAP-IV, ADHD combined symptoms (mean difference -0.009 95%CI [-0.191, 0.173], p=0.921) or any other measure. Small, non-significant, benefits of NFPP over TAU were seen for parent-rated SNAP-IV, ADHD combined symptoms (-0.189 95%CI [-0.380, 0.003], p=0.053). NFPP significantly reduced parent-rated conduct-problems compared to TAU across scales (p-values<0.05). No significant benefits of IY over TAU were seen for parent-rated SNAP, ADHD symptoms (-0.16 95%CI [-0.37, 0.04], p=0.121) or parent-rated conduct-problems (p>.05). The cost per family of providing NFPP in the trial was significantly lower than IY (£1,591 versus £2,103). Conclusions: Although, there were no differences between NFPP and IY with regards clinical effectiveness, individually-delivered NFPP cost less. However, this difference may be reduced when implemented in routine clinical practice. Clinical decisions should take into account parental preferences between delivery approaches. Funding: National Institute of Health Research. Trial Registration: Trial name: COPPI Trial; ISRCTN39288126.